Pengaruh Land Subsidence terhadap Genangan Banjir dan Rob di Semarang Timur - Pujiastuti, ratih; Suripin, Suripin; Syafrudin, Syafrudin (MEDIA KOMUNIKASI TEKNIK SIPIL, 2015)
Inundation of flood and rob (flood due to high tides) in Semarang City is increase wtithin area and depth. It be more seroius condition because of land subsisdence that happened in coastal area of Semarang City. This research is foccused on prediction and mapping of inundation flood and rob due to land subsidence effect in East Semarang, especially Tenggang Watershed and Sringin Watershed. On this research, data analysis including analysis of land subsidence, analysis of hydrological data, analysis of flood discharge with HEC-HMS, hydraulics analysis with HEC-RAS and then mapping the results of the flood inundation with Arc GIS. The inundation will be create with overlay the DEM of flood water level and DEM of topographic. According to the results of analysis is known that minimum land subsidence is 0 cm/year that happened in south area of Semarang and more higher ini north area with maximum land subsidence is 5.58 cm/year. On periode   2014-2031, the contribute of land subsidence to increase the inundation of flood and rob is 1.39%/year.